The dialogics of satire : foci and faultlines in George Orwell's Animal Farm and Nineteen Eighty-Four - Goodman, Ralph (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD)--Stellenbosch University, 2000.